لترقية مهارة القراءة IMAGE DESCRIPTION CHAIN باستخدام وسيلة التعليم TEAM ASSISTED INDIVIDUALIZATION (TAI) فعالية طريقة - Ni’mah, Khoirotun; Junaedi, Junaedi (Prodi Pendidikan Bahasa Arab FTK UIN Sunan Ampel, 2020)
writing skills are one of the most difficult language skills for students, this is because students must be able to choose the right diction and master the complex rules of Arabic grammar to be able to compose Arabic sentences properly and express what in their mind in writing. The team Assisted Indivualization method is one of the methods that emphasizes cooperative learning, while the ChainImage Description media is one of the learning media thatcan stimulate students to think and describe an object. Therefore, this study discuss the Team Asissted Individualization method using Chain Image Description media to improve writing skills. This study uses quantitative methods. Data collection techniques used were observation, interviews, documentation and tests. The population in tihis study were student’s of MTs DarulUlum Waru Sidoarjo, while the sample was class 7A. The effertiveness in the application of the Team Assisted Individualization method using Chain Image Description media with the results of T-Count=16 from the results of the analysis using the T-Test. And from here itcan be seen that T-Count is greater than the T-Table and this shows that the hypothesis HO is rejected and the hyphotesis Ha is accepted.